Effect of biocomposite mat erials to enhance durability of selected wood species (Intsia Palembanica Mio,Neobalanocarpus Heimii, Shorea Plagata)in Malaysia - Nik Haneez Amizan Nik Rosdi; Mazlan Mohamed; Marinah Mohamad; Mohd Hazim Mohamad Amini; M.S. Abdul Aziz; Zairi Ismael Rizman (2015)
The purpose of this study is to improve the recent technology which only used the solid wood as a product like bridge, water tanks, furniture, and others that might have some lacking. It is also to determine the wood properties in terms of durability in mechanical properties when combining with wood composite materials. Recent studies show that the wood itself have some disadvantages of wood properties, which covers the solid wood will get moulds, easily broken, not flexible, not durable because of termite attacks, and others. In those researches, they stated that the disadvantages of using wood fibers are their low bulk density, low thermal stability, high tendency to absorb moisture, and susceptibility to biological degradation. Thus, this research study aims an innovation, which is to determine and compare the impact of different wood composites when laminating with different type of solid wood, so that it can be applied to the industry when the durability is enhanced. In order to get most accurate result, this study used SolidWorks simulation software to predict the suitability of bio composite materials. Method used in the experiment is by using Charpy impact test, to figure out the energy needed to fracture the samples. The energy then is converted to Force (N) to find the stress value. The value also needed to be included as parameters like force and type of woods in simulation design. Combination of Merbau wood and plywood is determined as the most effective bio composite material because the value increase up to 41.57%. SolidWorks simulation also had predicted the value well with the percentage difference only from 1.14% until 23.24% from the experimental design